2022
DOI: 10.1002/jmcd.12235
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping, and the Strong Black Woman: An empirical analysis

Abstract: The Strong Black Woman icon presents an image of Black women as infrangible, able to endure hardships unscathed, and in possession of indomitable strength. In this quantitative study of 100 Black women, statistically significant relationships were found between Strong Black Woman attitudes and stress. Implications for Strong Black Women clientele in a professional counseling context are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Consequently, this cultural narrative of the SBW could influence how African American women perceive stress and choose to adopt coping strategies, thereby shaping their overall methods to manage adversity. For instance, Graham et al (2022) demonstrated a relationship where an increased adherence to the SBW narrative corresponded with escalated stress levels among African American female participants. They stressed the concept of collective coping, suggesting that some women, under the influence of SBW beliefs, mitigate stress by leaning on family and social networks for support.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this cultural narrative of the SBW could influence how African American women perceive stress and choose to adopt coping strategies, thereby shaping their overall methods to manage adversity. For instance, Graham et al (2022) demonstrated a relationship where an increased adherence to the SBW narrative corresponded with escalated stress levels among African American female participants. They stressed the concept of collective coping, suggesting that some women, under the influence of SBW beliefs, mitigate stress by leaning on family and social networks for support.…”
Section: Discussionmentioning
confidence: 99%